Mouse period1 gene expression recording from olfactory bulb under free moving conditions with a portable optic fibre device. (22nd June 2020) - Ito, Ryoga; Hamada, Kazuko; Kasahara, Shigeru; Kikuchi, Yoshihiro; Nakajima, Kanako; Sutherland, Kenneth; Shirato, Hiroki; Ozaki, Michitaka; Ishikawa, Masayori; Hamada, Toshiyuki
Abstract: Because the disruption of circadian clock gene is a risk factor in many diseases such as obesity and cancer, it is important to monitor and analyzed the expression of the rhythm of the clock gene throughout the body over a long period of time. Although we previously reported on a new gene expression analysis system tracking a target position on the body surface of freely moving mice, the experimental apparatus required a large space. We have therefore developed an in vivo recording system using a portable photomultiplier tube (PMT) system attached to an optical fibre. Directly connecting the target area with the device, we could easily measure the photon counts in a very small space. However, little information is known about the characteristics of optical fibres when exposed to twisting/looping in association with a moving mouse and the effect of the surface of optical fibre. In the present study, we report on the characteristics of optical fibres to detect gene expression rhythm in freely moving mice. Using this portable optical device directly connected with a target area, we were able to measure the circadian rhythm of clock gene expression over a prolonged period in freely moving mice in a small space.